Woodlot devolution in Northern Ethiopia: opportunities for empowerment, smallholder income diversification and sustainable land management - Jagger, Pamela; Pender, John L.; Gebremedhin, Berhanu (International Food Policy Research Institute, 2003)
This paper explores the patterns and determinants of empowerment, income generation, and environmental sustainability under varying degrees of woodlot management in Tigray, Ethiopia. Our analysis is based upon a survey of 120 collectively managed woodlots, devolved to varying degrees, and 66 households that have recently received small plots of community land for tree planting. We find that more devolved woodlot management empowers resource users by providing greater autonomy regarding the management of woodlots, and in particular the ability to make decisions about the harvest of woodlot products. Our economic analysis indicates that grass is by far the most important product being harvested from woodlots. There has been very limited harvesting of higher value products such as poles and fuelwood, which are in very short supply in the region. Labor inputs declined, and average annual net benefits improved as woodlots were more devolved, indicating that devolved woodlots are more economically efficient. Woodlots were generally perceived to be associated with positive changes in environmental conditions such as the slowing of erosion and gully formation, and the maintenance of biodiversity. However, greater environmental benefits were associated with less devolved woodlots. This study highlights the trade-offs inherent in varying levels of woodlot management. Though woodlots are perceived to provide significant environmental functions, restrictions regarding harvesting high value products are limiting the potential for smallholder income diversification and empowerment, two critical components of poverty alleviation in Ethiopia.